2009
DOI: 10.1111/j.1365-2699.2008.01983.x
|View full text |Cite
|
Sign up to set email alerts
|

Do migratory pathways affect the regional abundance of wintering birds? A test in northern Spain

Abstract: Aim  The abundance distribution of organisms at regional scales is commonly interpreted as the result of spatial variation in habitat suitability. However, the possibility that geography itself may affect patterns of distribution has received less attention. For example, the abundance of wintering bird populations might be influenced by the cost of reaching areas located far away from the main migratory pathways. We studied the abundance distribution of three common migratory passerines (meadow pipits, Anthus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…Small and isolated populations of southern Italy, despite the increasing number, could be considered as small patches of this metapopulation system cut off from the bulk of the population of Western Europe. As a matter of fact, distribution and abundance of migrants could be influenced by the cost of reaching areas located far away from the main migratory pathways (Henningsson and Alerstam 2005a, b;Tellerı´a et al 2009) and several studies show that isolation could lead small and periphery patches to local extinction (Lomolino et al 1989;Peltonen and Hanski 1991;Hanski et al 1995;Whitcomb et al 1996;Smith and Gilpin 1997;Thomas and Hanski 1997;Hanski 1998;Dunham and Rieman 1999;Clinchy et al 2002;Wahlberg et al 2002). In support of this hypothesis, historical data confirm that the short-toed snake eagle was breeding in areas of southern continental Italy and Sicily at least until the end of the 19th century (Salvadori 1872; Lucifero 1898; Arrigoni degli Oddi 1929) while current data show that it is no longer found in those areas.…”
Section: Ecological Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Small and isolated populations of southern Italy, despite the increasing number, could be considered as small patches of this metapopulation system cut off from the bulk of the population of Western Europe. As a matter of fact, distribution and abundance of migrants could be influenced by the cost of reaching areas located far away from the main migratory pathways (Henningsson and Alerstam 2005a, b;Tellerı´a et al 2009) and several studies show that isolation could lead small and periphery patches to local extinction (Lomolino et al 1989;Peltonen and Hanski 1991;Hanski et al 1995;Whitcomb et al 1996;Smith and Gilpin 1997;Thomas and Hanski 1997;Hanski 1998;Dunham and Rieman 1999;Clinchy et al 2002;Wahlberg et al 2002). In support of this hypothesis, historical data confirm that the short-toed snake eagle was breeding in areas of southern continental Italy and Sicily at least until the end of the 19th century (Salvadori 1872; Lucifero 1898; Arrigoni degli Oddi 1929) while current data show that it is no longer found in those areas.…”
Section: Ecological Parametersmentioning
confidence: 99%
“…Ecological niche is related to several different factors, including foraging and nesting opportunities. The probability of colonization depends on the dispersal abilities of the species and its dispersal behaviour, as well as geographic features such as natural barriers (Alerstam 1990;Tellerı´a et al 2009). Therefore, the current biogeographical patterns might be explained by hypotheses that are related to environmental, morphological and historical data (Cumming et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we test if the distance to the main autumnal migratory flyway of black storks crossing Iberia affects the size of wintering aggregations. Previous analyses have reported that areas close to the migratory flyways are more densely occupied in the winter by some migratory birds (Galarza and Tellería , Tellería et al ). We try to demonstrate that, in addition to the effect of environmental suitability, the areas close to the main flux of migratory storks have more wintering individuals than the areas located in distant positions.…”
mentioning
confidence: 95%
“…After visual inspection of the patterns, we explored whether breeding and wintering ranges had a parallel distribution (western populations inhabit the westernmost wintering grounds compared to eastern populations). For this purpose, we correlated the mean longitudinal coordinates provided by the detection of each individual in breeding and wintering areas (Table 3; see Tellería et al 2009 for a similar approach).…”
Section: Resultsmentioning
confidence: 99%